Persepsi Efektivitas Penggunaan Media Virtual Reality - Theresia Sunarni; Dominikus Budiarto (Performa: Media Ilmiah Teknik Industri, 2014)
This study is describting of using VR media to improve the effectiveness of learning in the course of manufacturing processes. VR media are used based on specific competency goals in the Event Unit Class (SAP) courses manufacturing process. VR Media (prototype) can be a bridge between the theoretical material in the classroom with laboratory or industrial conditions in actual reality. With VR media is expected that students can improve their learning performance. The use of VR media in the learning manufacturing process course, carried as a complement or supplement. The questionnaire model is developed, then a questionnaire is distributed to students who have been following and using VR media in the learning. From the questionnaire data processing has been obtained: the result of the perception of the effectiveness of this VR media in selected university, indicating (1) to achieve successful learning with VR media, it needs proper planning and methods. Constructivism learning using VR media can be said to be effective ("learning success") if it satisfies some of the indicators that is effective, efficient (feasible and does not require effort/many effort), the performance of both media (has appeal). (2) Regarding the perception of the effectiveness of learning by using VR media in learning, the respondent's answer to this is pretty good (quite effectively) to achieve the target competencies, and if the sample has been comprehensively would be better (effective) in achieving the targeted competencies. Advices are given based on the results of this study for further development, namely: for non-constructivism learning effectiveness is not yet known how the role of the media and the results when using VR, need to be investigated further learning how to achieve effective, efficient and attractive.